Decoding #BlackGirlMagic: an analysis of how Black women at a South African university construct and celebrate their identities through the hashtag - Kayumba, Urielle Ngoie (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies)
The emergence of the Black Girl Magic hashtag in 2013 marked a pivotal moment in the realm of social media, igniting a powerful movement that resonated far beyond the digital sphere. This hashtag, which initially gained traction on platforms like X/Twitter and Instagram, served as a catalyst for celebrating the multifaceted achievements and resilience of Black women. The profound impact of this movement on an individual level became the focal point of my personal journey, delving into the transformative effects of #BlackGirlMagic within the context of a media landscape historically characterised by a lack of diverse representation. The study takes a closer look at the significance of the hashtag in fostering a sense of acceptance among Black women. In a world where mainstream media has perpetuated narrow beauty standards and marginalised narratives, #BlackGirlMagic emerged as a beacon of empowerment (Mason, 2021). This research does not shy away from acknowledging the complex and nuanced dimensions inherent in this movement. It explores how factors such as featurism, colourism, texturism, body types, and nationalities intersect with the celebration, recognising that while #BlackGirlMagic champions empowerment, it also grapples with inherent limitations that need to be addressed (Sinon, 2020). The study explores how Black women students at Rhodes University use and understand the hashtag #BlackGirlMagic in their lives. The research considers the experiences and cultural practices of Black women in online spaces (Bevins, 2020). By delving into the ways in which they engage with #BlackGirlMagic, the study explores the digital landscape as a dynamic and evolving arena where identity, empowerment, and representation intersect. This approach allows for a deeper comprehension of the lived experiences of Black women in the online realm, shedding light on how Black women students at Rhodes University use #BlackGirlMagic and the challenges they face in seeking to be included and represented. By focusing on the experiences of Black women students at Rhodes University, the research can contribute to the broader discourse on digital activism and the role of social media in shaping contemporary feminist movements. This localised perspective offers valuable insights into how global movements like #BlackGirlMagic are adapted and reinterpreted within specific cultural and institutional contexts, highlighting the importance of digital spaces as sites of both empowerment and contestation for Black women.
Keywords: Black Girl Magic; Identity formation; Identity (Psychology); Empowerment; Women, Black; Representation (Philosophy)